Bacterial Translocation as Inflammatory Driver in Crohn’s Disease - Linares, Raquel; Francés, Rubén; Gutiérrez, Ana; Juanola, Oriol (Frontiers in Cell and Developmental Biology, 2021)
Crohn’s disease (CD) is a chronic inflammatory disorder of the gastrointestinal tract responsible for intestinal lesions. The multifactorial etiology attributed to CD includes a combination of environmental and host susceptibility factors which result in an impaired host-microbe gut interaction. Bacterial overgrowth and dysbiosis, increased intestinal barrier permeability and altered inflammatory responses in patients with CD have been described in the past. Those events explain the pathogenesis of luminal translocation of bacteria or its products into blood, a frequent event in CD, which, in turn, favors a sustained inflammatory response in these patients. In this review, we navigate through the interaction between bacterial antigen translocation, permeability of the intestinal barrier, host’s immunologic response and the genetic predisposition as a combined effect on the inflammatory response observed in CD. Several evidences support that translocation of bacterial products leads to uncontrolled inflammation in CD patients and, as a matter of fact, the presence of gut bacterial genomic fragments at a systemic level constitutes a marker for increased risk of relapse among CD patients. Also, the significant percentage of CD patients who loose response to biologic therapies may be influenced by the translocation of bacterial products, which are well-known drivers of proinflammatory cytokine production by host’s immune cells. Further mechanistical studies evaluating cellular and humoral immune responses, gut microbiota alterations and genetic predisposition will help clinicians to better control and personalize the management of CD patients in future.